Perceived vulnerability and intention of use protective behavioral strategies among Spanish young adults: The mediating role of drinking motives - González Ponce, Bella (2023)
Perceived vulnerability to alcohol consequences, a central factor in Protection Motivation Theory can motivate people to adopt health-protective behavior. However, systematic review showed that perceived vulnerability is a poor predictor of intention and behavior. From a motivational perspective on alcohol use, perceived vulnerability can be affected by reasons people have drinking. For example, previous studies showed that drinking motives predict perceived vulnerability, and drinking motives are associated with high protective behavioral strategies (PBS) use. Thus, drinking motives would explain the relationship between perceived vulnerability and intention to use PBS. The present study examines if drinking motives (social, enhancement, coping, and conformity) mediate the relationship between perceived vulnerability and intention to use PBS. Prospective design with a baseline assessment and a 2-month follow-up. We recruited 328 young adults (age: M = 21.15; SD = 2.23) who completed questionnaires to measure perceived vulnerability to negative consequences when consuming alcohol, and when getting drunk and drinking motives at baseline, and intention to use PBS at follow-up. Mediation analyses showed that higher perceived vulnerability was related to higher positive motives (social and enhancement), which was related to lower intention PBS use. Negative motives for drinking (coping and conformity) did not mediate this relationship. Our findings support the usefulness of correcting self-perceptions risk of alcohol use in interventions aimed at reducing alcohol-related harm in young adults, and drinking positive motives should be included as a component of these interventions.